Secular changes in body size and menarche age of Javanese adolescent in Yogyakarta - Neni Trilusiana Neni Trilusiana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Secular changes observed in human development are very sensitive bioindicators of social stresses, social and economic changes, as well as pollution and transformation of the natural environment. Environmental factors, such as nutritional habits, lifestyle and infectious diseases appear to be the main causes of differences in growth and maturation between ethnic and social groups. Objectives: This study was undertaken to know the secular changes in body size and menarche age of Javanese adolescent in Yogyakarta.Methods:The sample consisted of 562 Yogyakarta adolescent (300 girls and 262 boys), ranging from 11 to 18 years of age, measured in August - September 2005. For comparison, data on body size and menarche age of Yogyakarta adolescent examined in 1982 by Aswin et al were used. Measurements of stature and height, and menarche age were obtained for two samples of the Yogyakarta adolescent. Means and standard deviation were calculated for each measurement and for menarche age. Results: The results for stature, weight and menarche age of adolescent measured in 2005 wee greater compared with other Javanese Yogyakarta samples adolescent 23.years ago. Significant positive trends instature, weight and menarche age were apparent between the two samples: 7.37 cm (5.1                        %),  9.21   kg(26.1   %) and 16.6 months (10.6 %), respectively.Conclusions: In summary, the results show a positive secular trend in body dimensions (height and weight) and menarche age, and this can be related to improvement in living conditions in Yogyakarta, especially during the last 23 years. Key words: secular change - anthropometric - menarche age - adolescent